Pemanfaatan Komposter Sederhana untuk Mendukung Pengelolaan Limbah Organik sebagai Pupuk Organik di Nagari Harau - Riza Syofiani; Fastabiqul Khairad; Hudia Hudia; Dyah Puspita Sari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Organic waste management in rural communities, especially those dependent on the agricultural sector, is still a big challenge. Organic waste such as crop residues, leaves and household waste are often not utilized optimally, resulting in environmental pollution and wasted potential. Meanwhile, farmers' dependence on chemical fertilizers increases production costs and reduces soil quality in the long term. This service program aims to provide education and assistance to farmer groups in Nagari Harau regarding the use of simple composters as a solution for managing organic waste. A simple composter is a method that is easy to make, cost effective, and can produce compost that is rich in nutrients. A participatory approach is used in implementing this program to ensure active community involvement in the entire process, from waste collection, composting, to utilization of the results. Through this program, it is concluded that communities can be more independent in managing organic waste, reduce negative impacts on the environment, and increase productivity and overall welfare of farmers.